Chromosomal microarray detects genetic risks of neurodevelopmental disorders in newborns with congenital heart disease. (4th August 2021) - Gill, Kamalvir; Sasaki, Jun; Jayakar, Parul; Sosa, Lisa; Welch, Elizabeth
Abstract: Objective: To compare the genetic testing results of neonates with CHD by chromosomal microarray to karyotyping and fluorescence in situ hybridisation analysis. Methods: This was a single-centre retrospective comparative study of patients with CHD and available genetic testing results admitted to the cardiac ICU between January, 2004 and December, 2017. Patients from 2004 to 2010 were tested by karyotyping and fluorescence in situ hybridisation analysis, while patients from 2012 to 2017 were analysed by chromosomal microarray. Results: Eight-hundred and forty-nine neonates with CHD underwent genetic testing, 482 by karyotyping and fluorescence in situ hybridization, and 367 by chromosomal microarray. In the karyotyping and fluorescence in situ hybridisation analysis group, 86/482 (17.8%) had genetic abnormalities detected, while in the chromosomal microarray group, 135/367 (36.8%) had genetic abnormalities detected (p < 0.00001). Of patients with abnormal chromosomal microarray results, 41/135 (30.4%) had genetic abnormality associated with neurodevelopmental disorders that were exclusively identified by chromosomal microarray. Conotruncal abnormalities were the most common diagnosis in both groups, with karyotyping and fluorescence in situ hybridisation analysis detecting genetic abnormalities in 26/160 (16.3%) patients and chromosomal microarray detecting abnormalities in 41/135 (30.4%) patients (p = 0.004). In patients with d-transposition of the great arteries, 0/68 (0%) were found to have genetic abnormalities by karyotyping and fluorescence in situ hybridisation compared to 7/54 (13.0%) by chromosomal microarray. Conclusions: Chromosomal microarray identified patients with CHD at genetic risk of neurodevelopmental disorders, allowing earlier intervention with multidisciplinary care and more accurate pre-surgical prognostic counselling.